Growth effects of financial market instruments: The Ghanaian experience - Ekundayo P. Mesagan; Isaac A. Ogbuji; Yasiru O. Alimi; Anthonia Taye Odeleye (African Governance and Development Institute (AGDI), 2019)
This study analyses the growth effects of financial market instruments in Ghana between 1991 and 2017. We use the ARDL bounds testing approach to analyse data on real GDP per capita, monetary policy rate, treasury bill rate, stocks traded, bank credits, stock turnover, market capitalisation, foreign direct investment, and gross investment. Findings show the existence of a long-run relationship between both short- and long-term financial market indicators and economic growth. Also, results confirm that long-term financial instruments perform better than the short-term instruments in boosting the country's economy in the short-run, while in the long-run, both short-term and long-term financial indicators positively impact economic growth in Ghana. We recommend that the bank of Ghana should consider lowering the bank rate further from the current annual rate of 16.0% to enhance bank credits, boosts domestic investment, and improve growth in the long-run.
Keywords: E13; E43; E51; G20; O47; 330; Financial Market Instruments; Market Capitalisation; Economic Growth; ARDL Bounds Test